Analysis Of The Growth Rate Of Hotel Tax and Advertising Tax In Ambon City - Anna Valensia Christianty De Fretes (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to look at the rate of tax growth on the realization of hotel tax receipts and real estate tax of Ambon City District during the period 2018-2022. This study is a quantitative study whose results can be accounted for in numbers. Population and sample research is a report on the realization of receipts of hotel tax and advertising tax in the year 2018-2022. Data collection techniques using data collection techniques such as Time Series, Documentation and Library Studies. The research shows that the highest rate of growth of hotel tax is in 2021 at 33.59%. This figure falls in the category “Less Successful” while the advertising tax has the greatest percentage of 17.40% but this figure is in a category below 30% which means in category “No Success”. For that, the local government is expected to reevaluate and maintain the regional tax so that it can rise to the category of success or very success.